Prerequisites For The Occurrence And Counterfeit Of Corruption: Historical And Legal Aspects - Gryschuk, Maksym (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article analyzes the historical preconditions for preventing and combating corruption in the world and in Ukraine. The author came to the conclusion that the problem of corruption of officials has existed since ancient times. This is due to the emergence of certain categories of society with greater powers, which allowed to influence important issues. It can be stated that practices considered by scientists to be corrupt accompany the entire economic history of mankind. Evolving, corruption from individual, sporadic manifestations in the form of bribery, has become a complex, systemic, multifaceted phenomenon of both local and global dimensions. However, it was not until the 1990s that certain publications began to identify and recognize corruption as an integral feature of any system and development of society. The current state of corruption in Ukraine is largely due to long-standing trends and the transition from a totalitarian to a democratic form of government. Analyzing the above material, in our opinion, among the most important factors that determine the growth of corruption and have historical roots, in addition to dysfunctions of the state machine and some historical and cultural traditions, include: urgent transition to the new economic system, not fully provided with the necessary legal framework and legal culture; the absence of a normal legal system in Soviet times and the presence of relevant cultural traditions; branching of the bureaucratic system and weakening of the party control system; legal nihilism and legal ignorance of the general population.